Artificial intelligence to improve rehabilitation care for children with developmental conditions: Some ethical considerations. (20th July 2022) - van der Veen, Sabina; van der Leeden, Marike; Geleijn, Edwin; Vossen, Piek; Meskers, Carel G. M.; Widdershoven, Guy A. M.
Abstract : This commentary is on the original article by Greve et al. on pages 100‐106 of this issue.